Improvement of properties and olfactory attributes of isolated protein from edible insects by roasting - Ganbat, Chinbat; Han, Jung-Ah (Food science and biotechnology, 2025)
The characteristics of proteins extracted from two kinds of edible insects ( and , for G.B and T.M, respectively) were compared after roasting at 180 °C for 15 min and 200 °C for 10 min, respectively. The amino acid content decreased by roasting, and the degree of decrease varied depending on the type of edible insect and roasting temperature. Antioxidant activity increased by 5.2-11.3% following roasting, with no significant differences by roasting temperature. The results of Infrared (IR) spectrum and gas chromatography (GC) analysis revealed that compounds contributing to a strong waxy scent and sour taste decreased, whereas those associated with aroma and floral scent increased as a result of roasting. In conclusion, roasting led to an enhancement in the olfactory characteristics of proteins extracted from edible insects, and roasting at 180 °C for 20 min for G.B and 200 °C for 15 min for T.M could be considered optimal.